THE CONCEPTS OF ISLAMIC EDUCATION FROM THE PERSPECTIVE OF IBNU MISKAWAIH - Putri, Yulita; Nurhuda, Abid; Syukron Ni'am (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2023)
The Umayyad dynasty became a historical record in the development of science, even spurring the birth of the golden age of Islam in which many figures and scholars emerged who not only understood religious knowledge, but were also very interested in education. One of them is Ibn Miskawaih. So the purpose of this study is to describe the concept of Islamic Education in the Perspective of Ibnu Miskawaih. The method used is descriptive qualitative with a literature study approach then the data is collected, followed by analyzing the contents and the last is drawing conclusions. The results of the study show that the concept of Islamic education in the perspective of Ibnu Miskawaih is more dominated by the aspect of cultivating morals based on the Qur'an and referring to al-hadith so that someone who is educated can become a complete human being. In addition, it must be supported by 3 important components in education, namely family education which cultivates one's habits from childhood, school education where one can get to know the concept of reward and punishment and finally environmental education which becomes a place of practice from one's results in education and learning. in the middle of society.